Sex for sale prostitution, pornography, and erotic dancing - Weitzer, Ronald John 1952- (Routledge Books, 2023)
Since the publication of the second edition in 2010, the field of sex work studies has expanded. This fully updated edition of Sex for Sale: Prostitution, Pornography, and Erotic Dancing presents an innovative, in-depth, and nuanced analysis of sex work, its risks, and benefits, and pays attention to newer and everchanging types of sex work and its actors, as well as public policies and laws that govern its trade. Now in its third edition, this volume includes updated research on traditional forms of sexual labor and incorporates original, empirically grounded research on newer or less researched phenomena. New chapters explore the use of technology among street sellers, blurring the line between street and online solicitation, in addition to chapters on historical prostitution, transgender workers, illicit massage parlors, male strippers, commercial webcamming, alternative policies and legal systems, and the sex workers' rights movement. The combination of cutting-edge and comprehensive analyses and carefully constructed methodologies in Sex for Sale makes it an excellent source of information for scholars and university students in gender studies, sociology, and criminology